Up-down ordered Chinese Restaurant Processes: representations and asymptotics - Rogers, DJ (2020)
We study composition-valued Markov chains that appear naturally in the frame-work of up-down Chinese Restaurant Processes (CRPs), introducing first discrete time models as in a similar way to those introduced by Petrov (2009), and also in continuous time via a Poissonisation technique similar to that used in Pal (2011).